Analysis of marketing channels and income of catfish farming business of Sangkuriang Bhakti farm perspective of islamic economic law - Rizky, Farid Al; Aziz, Abdul (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2024)
This study aims to analyse the marketing efficiency and income of sangkuriang catfish farming business in Bhakti Farm Ciledug, Tangerang from the perspective of Islamic economic law. The research was conducted from December 2022 to March 2023 using qualitative and quantitative methods through a case study approach and interview techniques with business owners. The results identified two marketing channels, namely: (1) Cultivators - middlemen - large traders - small traders, and (2) Cultivators - small traders. Marketing efficiency analysis showed that both channels were efficient with an EP value of <1, where marketing channel II (Cultivators - small traders) was more efficient with an EP value of 0.075 and a marketing margin of IDR 5,000. In terms of income, production in the harvest period averaged 5,062 kg with production costs of Rp. 58,541,000 and revenue of Rp. 96,178,000 (selling price of Rp. 19,000/Kg). The income received by Bhakti Farm with a pool area of 210 m2 is Rp. 37,596,600, which means TR> TC, so that the sangkuriang catfish farming business at Bhakti Farm is proven to be profitable. In the perspective of Islamic economic law, Bhakti Farm's marketing practices must be transparent, fair, and avoid prohibited elements such as usury, gharar, and maysir. Profits obtained must be halal and not harm other parties. The fish farming business must also be environmentally friendly and provide benefits to the welfare of the surrounding community. In addition, Bhakti Farm is expected to apply Islamic business ethics such as honesty, trustworthiness, and professionalism in running its business.Kata Kunci: Marketing Channel; Marketing Margin; Marketing Efficiency; Production Cost; Islamic Economic Law.